Avaliação e desenvolvimento de catalisadores nanoporosos ácidos para obtenção de ésteres sintéticos lubrificantes a partir do ácido ricinoléico - Saboya, Rosana Maria Alves (2016)
Currently, the domestic market of basestock oils and finished lubricants has accompanied the world increasing demand for lubricants obtained from renewable sources and higher quality products, bio-lubricants. Synthetic esters form a large group of products, which can be either from petrochemical or oleochemical origin. Due to the wide interest in environmentally friendly products, synthetic esters derived from vegetable oils have received special attention. However, this raw material can compete with the chain of the food industry. This fact has generated great efforts in the development of products from sources that do not interfere in the food industry. In this sense, from the castor bean is obtained one of the most important nonedible oils. The great interest in this oil is also attributed to the high ricinoleic acid content (≈ 90 %). The ricinoleic acid has been reported in the literature as the feedstock to esterification reaction for biodiesel production using short chain alcohols in the presence of mineral acids such as H2SO4. However, the use of alcohols with C8 to C14 is more interesting for the production of esters when the aim is its use as lubricant. In this study the esterification reaction of ricinoleic acid with 2-ethylhexanol with various solid acid catalysts was evaluated. This study focused on synthesis of acid catalysts using two types of support: mesoporous silica SBA-15 and porous clay heterostructures (PCH). Comparative studies were also carried out for commercial catalysts such as ion-exchange resins. It has been synthesized a set of WO3 based catalysts supported on porous clay heterostructured with different zirconium contents in their pillars. The catalysts with a tungsten content of 20 wt.% and a molar ratio Si/Zr = 15 in the pillars exhibited the highest conversion, reaching a conversion value close to 60 and 91 % after 8 and 24 h, respectively. SBA-15 silica synthesized by different procedures was used as catalytic support in the preparation Nb2O5 catalyst. The catalyst prepared by hydrothermal method with niobium oxide content of 12 wt.% exhibited the highest conversion, reaching a conversion value 80 % after 8 h. Among the evaluated resins, Amberlite-15 showed the best catalytic performance in terms of conversion of ricinoleic acid. The resins were quite active in the reaction of esterification of ricinoleic acid with 2-ethyl-1- hexanol. Such activity may be related to a homogeneous small contribution due to leaching of sulfonic acid groups in the reaction medium